Canada : Financial Sector Assessment Program-Technical Note-Systemic Liquidity. (IMF Staff Country Reports; Country Report ;, 2020)
This Technical Note on Financial Safety Net and Crisis Management for the Canada examines systematic liquidity issues. The review evaluated the Bank of Canada's (BOC's) operational framework and its ability to manage liquidity conditions in normal times and in times of stress. The review also assessed the functioning and resilience of key funding markets in Canada. The paper highlights that the BOC's framework for market operations and liquidity provision in normal times is comprehensive and well-articulated. System-wide liquidity conditions are stable, market rates are closely aligned with the announced policy rate, and the BOC has many channels to provide liquidity against a broad range of collateral. Foreign exchange markets appear liquid, and their resilience is increasingly important given the growing reliance on external, foreign-currency funding. Contingency plans for market-wide liquidity support regarding intervention in securities markets and provision of foreign-currency liquidity should be developed further and tested.